2012
DOI: 10.2478/s11756-011-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of larval jelly antimicrobial peptide defensin1 in Apis mellifera colonies

Abstract: Honeybee brood food, larval jelly (LJ) contains antimicrobial peptide defensin1 that is able to inhibit in vitro growth of the pathogen causing American foulbrood (AFB). This fact suggests that LJ defensin1 could participate in defense of colonies against AFB. We assume that the potential defense function of defensin1 in vivo might depend on its amount in LJs. Therefore, we investigated the expression of defensin1 in colonies. The expression was examined on protein and mRNA levels in colonies of several Apis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…However, bee Def-1 significantly enhanced the secretion of MMP-9 from keratinocytes. Similar to MRJP1, Def-1 is a common but quantitatively variable factor present in both RJ and honey 8 , 28 . The concentration of Def-1 in RJ and honey varied in amounts ranging from 0.159 to 0.524 µg/mg 8 and 0.04 to 5.17 µg/g 28 , respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, bee Def-1 significantly enhanced the secretion of MMP-9 from keratinocytes. Similar to MRJP1, Def-1 is a common but quantitatively variable factor present in both RJ and honey 8 , 28 . The concentration of Def-1 in RJ and honey varied in amounts ranging from 0.159 to 0.524 µg/mg 8 and 0.04 to 5.17 µg/g 28 , respectively.…”
Section: Discussionmentioning
confidence: 97%
“…RJ has been used since ancient times to facilitate wound healing. RJ acts as an antimicrobial 4 – 8 and antioxidative agent 9 and as an immunomodulator with anti-inflammatory properties 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, defensin1, one of the major antibacterial factors in honey, was shown to be a regular but quantitatively variable component of each honey . One reason for the varying contents of defensin1 in different honeys seems to be constitutive but variable defensin1 expression in individual honeybees in bee populations . It has also been found that some types of honey derived from specific floral sources become more potent than others because of the presence of phytochemicals with antibacterial properties .…”
Section: Immumodulatory Compounds Of Various Honey Samples and Their mentioning
confidence: 99%
“…2 One reason for the varying contents of defensin1 in different honeys seems to be constitutive but variable defensin1 expression in individual honeybees in bee populations. 3 It has also been found that some types of honey derived from specific floral sources become more potent than others because of the presence of phytochemicals with antibacterial properties. [4][5][6] These potent natural honeys, such as manuka (Medihoney, Comvita NZ Ltd., Te Puke, New Zealand) and RS honey (Bfactory Health Products B.V., Rhenen, The Netherlands) (honey with unknown origin used as a source for Revamil), are currently being used as medical-grade honeys in clinical applications.…”
mentioning
confidence: 99%
“…Both nurses and foragers produce antimicrobial peptide defensin1 (Liu et al 2011;Klaudiny et al 2012;Majtan et al 2012). Nurses synthesize the peptide in their hypopharyngeal and mandibular glands (located in head) from which it is secreted into larval food -larval jelly (LJ) (Klaudiny et al 2005).…”
Section: Introductionmentioning
confidence: 99%